Motivation and extracurricular activity (ECA) involvement as predictors of the ECA-to-school interface in Singapore - Leow, Charmaine Jia Min (Nanyang Technological University, 2020)
Participation in extracurricular activities (ECA) is an increasingly prominent part of undergraduates’ university experiences. However, participation in ECAs is a double-edged sword, as it may bring about positive and negative inter-role effects. This study examines the role of motivation and involvement in the ECA-to-school interface. Studies have shown that students partake in ECAs due to varying motivations. Motivation can differentially affect psychological states, and in turn influence the inter-role interface. Drawing on the self-determination theory, intrinsic motivation was hypothesised to be positively associated with ECA-to-school enrichment (Hypothesis 1) and negatively associated with ECA-to-school conflict (Hypothesis 3). In contrast, extrinsic motivation was hypothesised to be negatively associated with ECA-to-school enrichment (Hypothesis 2) and positively associated with ECA-to-school conflict (Hypothesis 4). Further, hours of involvement and psychological involvement were hypothesised to be positively associated with both ECA-to-school enrichment (Hypothesis 5) and ECA-to-school conflict (Hypothesis 6). To test the hypotheses, data on students’ motivations for ECA involvement, involvement levels, and inter-role interface were collected from 139 undergraduates in Singapore through an online questionnaire. Intrinsic motivation was found to predict only ECA-to-school enrichment. Extrinsic motivation was found to predict only ECA-to-school conflict and this effect was exacerbated by hours of involvement. ECA involvement generally predicted both ECA-to-school enrichment and conflict. Findings suggest that ECAs are more beneficial when intrinsically pursued.